(untitled) (Olhares, 2025)
This article was prepared with the aim of presenting the reader with a brief panel of the life and work of Jorge Andrade, established as one of the main Brazilian playwrights since his debut in 1955, when his text A moratória was staged by Maria Della Costa Theater Company. The author also stood out for his work in education, journalism and television dramaturgy.